2024
DOI: 10.1101/2024.07.01.601572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The metabolic benefits of thermogenic stimulation are preserved in aging

Duraipandy Natarajan,
Bhuvana Plakkot,
Kritika Tiwari
et al.

Abstract: Adipose thermogenesis has been actively investigated as a therapeutic target for improving metabolic dysfunction in obesity. However, its applicability to middle-aged and older populations, which bear the highest obesity prevalence in the US (approximately 40%), remains uncertain due to age-related decline in thermogenic responses. In this study, we investigated the effects of chronic thermogenic stimulation using the β3-adrenergic (AR) agonist CL316,243 (CL) on systemic metabolism and adipose function in aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…To test this, we chose thermogenic stimulation using β3AR agonists, a method previously well-established to improve adipose and systemic metabolism in both rodents and humans 53 54 55 56 . Although the effects of β3AR agonists on systemic metabolism have only been well-characterized in young animals, our studies showed that it also effectively improved multiple metabolic parameters including adiposity, glucose metabolism, insulin sensitivity, circulating adiponectin, and ectopic lipid deposition 43 . More importantly, these systemic improvements were associated with improved microvascular endothelial function and cognition in aged mice, indicating that the beneficial effects of thermogenesis extend beyond metabolic tissues.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…To test this, we chose thermogenic stimulation using β3AR agonists, a method previously well-established to improve adipose and systemic metabolism in both rodents and humans 53 54 55 56 . Although the effects of β3AR agonists on systemic metabolism have only been well-characterized in young animals, our studies showed that it also effectively improved multiple metabolic parameters including adiposity, glucose metabolism, insulin sensitivity, circulating adiponectin, and ectopic lipid deposition 43 . More importantly, these systemic improvements were associated with improved microvascular endothelial function and cognition in aged mice, indicating that the beneficial effects of thermogenesis extend beyond metabolic tissues.…”
Section: Discussionmentioning
confidence: 69%
“…Addressing this, we have recently shown that the metabolic benefits of β3AR agonist treatment are preserved in aged mice. Chronic β3AR stimulation increased whole-body energy expenditure, reduced fat mass, improved glucose tolerance and insulin sensitivity, increased circulating adiponectin levels, and reduced ectopic lipid deposition in aged mice 43 . In the present study, we wanted to examine whether β3AR stimulationmediated improvements in systemic metabolism and circulating milieu can mitigate microvascular endothelial dysfunction and cognitive decline in aged mice.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation